Validity of single-beam timing lights at different heights - Altmann, S.; Spielmann, M.; Engel, F. A.; Neumann, R.; Ringhof, S.; Oriwol, D.; Haertel, S. (The Journal of Strength and Conditioning Research, 2017)
The purpose of this study was to quantify the effect of different timing light heights on sprint time and the validity of measurement. Two single-beam timing gate systems were used to measure 30-m sprint time (splits at 5 and 10 m) in 15 healthy and physically active male subjects. System 1 was set up at a height of 0.64 m and system 2 at 0.25 m (initial timing light) and 1.00 m (each following timing light), respectively. Participants performed 3 valid trials. The recordings of a high-speed video camera were used as a reference. Sprint times of system 1 and system 2 differed significantly between each other and from the reference system at all distances (p < 0.001). Intraclass correlation coefficients and Pearson's r values between both timing light systems and the reference system were low to moderate at 5 and 10 m and moderate to high at 30 m. Bland and Altman analysis revealed that the agreement intervals were considerably higher for the comparison between system 1 and the reference system than for system 2 and the reference system. A valid measurement of splits at 5 and 10 m via the systems used in this study is questionable, whereas 30-m times have an acceptable validity, especially when using system 2. This study confirms the influence of methodological approaches on sprint times. Coaches and researchers should consider that results gained by single-beam timing lights at different heights are not comparable.